Delizioishii Mushroom Enterprise / Mohd Khairul Fadhil Ondoy... [et al.] - Ondoy, Mohd Khairul Fadhil; Rusle, Nurlisa; Hashim, Siti Aishah; Anak Gon, Epah (2012)
Our business name is Delizioishii Mushroom Enterprise and has been operated since 2012. Our business is located at Bukit Mertajam. We are producing, packaging, selling and marketing fresh oyster mushroom and also oyster mushroom tempura. The factors why we are choosing this type of business because of market trend, consumers demand, less competitors and tremendous revenue opportunities. More detail about our business can be referred at our Executive Summary and business background. For Delizioishii Mushroom Enterprise, the Business Plan is a useful and versatile tool. It is a guide that can also be described as the businessman’s best friend. In today’s global and highly competitive business environment, enterprises, whether large or small, cannot hope to compete and grow without proper planning. Thus, this is what Delizioishii Mushroom Enterprise achieved and done; proper planning. Business Planning is fundamental to Delizioishii Mushroom Enterprise’s mission in assisting Delizioishii Mushroom Enterprise to start up, restructure and grow to become more competitive in line with Delizioishii Mushroom’s economic policy. Contrary to what some may think, a business plan is not a set of financial projections, an application for financial assistance and a guaranteed formula for success. Delizioishii Mushroom Enterprise sees the Business Plan as a thinking process performed by the enterprise for the enterprise itself. Every start-up enterprise needs to go through a thorough thinking process in order to come up with viable options and strategies that will strengthen its present position and facilitate its future development. Finally, the thinking process should culminate in a set of measures for the implementation of these strategies. This implementation plan is generally referred to as the milestone schedule. The milestone schedule should form both the starting and concluding point of planning process. In the first instance, well before we start writing the plan, we should make a list of all the things that we could possibly need in order to make our business a success. Once we have gone through the business planning process we will be in a much better position to identify and prioritize our needs in line with the realities of our business venture. All entrepreneurs think about their business. In fact, most businessmen do nothing else but brood and worry about problems and challenges that are the daily companions of every entrepreneur. To think about the business is not enough. It is important to think in a logical and structured manner, looking at every